2020
DOI: 10.1111/1759-7714.13357
|View full text |Cite
|
Sign up to set email alerts
|

Current status and progress of concurrent chemoradiotherapy in patients with locally advanced non‐small cell lung cancer prior to the approval of durvalumab

Abstract: Background: The standard treatment for patients with unresectable locally advanced (LA) non-small cell lung cancer (NSCLC) is chemoradiotherapy (CRT). Consolidation therapy with durvalumab after CRT demonstrated survival benefits and was approved in Japan in July 2018. The use of immune checkpoint inhibitors (ICIs) is entering routine oncological practice, and here we investigate the feasibility of concurrent CRT for LA-NSCLC patients based on the PACIFIC criteria. Methods: We performed a retrospective study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…3 pneumonitis were 58%, 26%, and 1% with a V20 constraint of 35%. 23 Another analysis of 31 patients found that pneumonitis occurred in 17.2% of all patients, and was of at least grade 3 in 6.9% of these patients. 24 In Table 4 we have summarized the incidence of pneumonitis associated with ICI consolidation therapy in Asian patients in different studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3 pneumonitis were 58%, 26%, and 1% with a V20 constraint of 35%. 23 Another analysis of 31 patients found that pneumonitis occurred in 17.2% of all patients, and was of at least grade 3 in 6.9% of these patients. 24 In Table 4 we have summarized the incidence of pneumonitis associated with ICI consolidation therapy in Asian patients in different studies.…”
Section: Discussionmentioning
confidence: 97%
“…These results thus suggest that ICI consolidation therapy is safe and feasible in Chinese patients. A Japanese retrospective analysis of 108 patients found that rates of grade 1, 2, and 3 pneumonitis were 58%, 26%, and 1% with a V20 constraint of 35% 23 . Another analysis of 31 patients found that pneumonitis occurred in 17.2% of all patients, and was of at least grade 3 in 6.9% of these patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Recently, durvalumab, a selective IgG1 monoclonal antibody which blocks PD-L1 binding to PD-1 and CD-80 allowing T cells to recognize and kill tumor cells, has been approved as the adjuvant standard of care after CRT with Level 1 proof for treatment of unresectable NSCLC. 42 To our best information, to date, no study particularly addressed the prognostic significance of PNI in NSCLC patients treated with the standard CRT followed by durvalumab or other immunotherapeutics. Nevertheless, neutrophil to lymphocyte ratio which is another inflammation index has been addressed as a prognostic indicator in some limited studies, [43][44][45] and a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients’ overall survival is less than 5 years whom were diagnosed at advanced stage [ 26 ]. Existing treatments extend the survival of part of patients with lung adenocarcinoma, but the overall curative effect is not so good, especially in the advanced cases [ 27 , 28 ]. The shortage of effective prognostic biomarkers to guide therapy is one of the reasons for the poor prognosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%